Beyond the Dimer and Trimer: Tetraspiro[2.1.25.1.29.1.213.13] hexadecane‐1, 3, 5, 7‐tetraone—the Cyclic Tetramer of Carbonylcyclopropane. Issue 12 (3rd February 2016) - Sedenkova, Kseniya N.; Averina, Elena B.; Grishin, Yuri K.; Andriasov, Kristian S.; Stepanova, Svetlana A.; Roznyatovsky, Vitaly A.; Kutateladze, Andrei G.; Rybakov, Victor B.; Albov, Dmitry V.; Kuznetsova, Tamara S.; Zefirov, Nikolay S.
Abstract: Tetraspiro[2.1.2 5 .1.2 9 .1.2 13 .1 3 ]hexadecane‐1, 3, 5, 7‐tetraone4, a unique tetraketone containing a cyclooctane core and four spiroannelated cyclopropane moieties, represents the previously unknown cyclotetramer of carbonylcyclopropane. For this purpose oxidation of the parent polyspirocyclic hydrocarbon was examined under various oxidative conditions, and the reactivity of oxidants towards methylene groups of the eight‐membered cycle, activated by adjacent spirocyclopropane rings, was evaluated and contrasted. Whereas the treatment of tetraspirohexadecane with ozone resulted in monooxidation, its reaction with methyl(trifluoromethyl)dioxirane afforded the product of four‐fold oxidation, triketoalcohol10 . Subsequent oxidation of the latter with Dess–Martin periodinane gave the target tetraketone4 . Abstract : A way to rotane ! Unknown cyclotetramer of carbonylcyclopropane was accessed from the parent hydrocarbon by the unprecedented oxidation of all four cyclopropane‐activated methylenes (see scheme).